(untitled) (Poornaprajna International Journal of Management, Education & Social Science (PIJMESS), 2025)
Purpose: The Karnataka State Road Transport Corporation (KSRTC) has decisively adopted the Unified Payment Interface (UPI) for its electronic ticketing machines (ETMs), revolutionizing the ticket purchasing process. KSRTC is an independent corporation established under Section 3 of the Road Transport Corporation Act of 1950, with operations commencing on August 1, 1961. On average, the corporation serves 35.43 lakh passengers each day, generating approximately ₹1,346.75 lakh in traffic revenue per day. Passengers can now buy tickets easily using QR codes and debit or credit cards, ensuring a seamless and convenient experience that aligns with several Sustainable Development Goals (SDGs), including gender equality (SDG 5), decent work and economic growth (SDG 8), industry, innovation and infrastructure (SDG 9), sustainable cities (SDG 11), peace, justice and strong institutions (SDG 16), and partnerships for the goals (SDG 17). This initiative also contributes to the growth of a cashless digital economy. As of October 2024, UPI has achieved remarkable milestones, processing a staggering value of ₹23.49 lakh crore and reaching a transaction volume of 16.58 crore. Its implementation across seven countries showcases its global impact and capacity to stimulate growth in various sectors, including B2B and B2C markets. KSRTC is leading the way by introducing a UPI-based ticketing system in collaboration with Ebix Cash Ltd. across four key divisions: KSRTC, NWKRTC, KKRTC, and BMTC. In the NWKRTC Belagavi division alone, passengers have completed 10.59 lakh payments, demonstrating the system’s widespread acceptance. As a state-owned pioneer in transport, KSRTC is among the first corporations in India to implement advanced digital payment solutions in partnership with the FinTech sector. This initiative firmly positions Karnataka at the forefront of the digital economy, driving social progress and advancing towards the Sustainable Development Goals. Design/methodology/approach: The research paper decisively examines both theoretical and empirical studies focused on a case study that highlights the significant impact of UPI digital payment services within the Karnataka State Road Transportation Corporation. It also emphasizes the vital role these services play in promoting sustainability. The analysis of UPI-based ticketing in KSRTC is conducted through the ABCD framework. Social Implications: The research decisively focuses on raising awareness and promoting inclusivity for passengers in both urban and rural areas through the implementation of the UPI digital payment system. Type of Paper: Exploratory Research Paper